POTENSI ANTIOKSIDAN DAN AKTIVITAS ANTIPROLIFERASI EKSTRAK KUNYIT PUTIH (Curcuma zedoaria Rosc.) PADA SEL HELA - Saefudin Saefudin; Fauzia Syarif; Chairul Chairul (Widyariset, 2014)
The aim of this study is to determine the antioxidant potential and anti-proliferative activity of Curcuma zedoaria Rosc extract on Hela cells. Two types of materials, such as water and ethanol extracts, were tested at different dose levels (1, 5, and 10%). The potential of antioxidant extract was tested by observing the peroxide value (POV) and prophylactic properties of superoxide (SO). The effects of Cytotoxic extracts were tested by observing the anti-proliferative properties on Hela cell morphology. Results showed that both water extract and ethanol extract contain antioxidants with higher value of superoxide and peroxide than a-tocopherol. Antioxidant potential of Curcuma zedoaria extract is evidential at its high concentration of 10%, but is less significant at lower concentration of 1 and 5%, when compared to the potential of positive control (a-tocopherol) and negative control (non-extract mixture). Antiproliferative activity of Curcuma zedoaria extracts at low concentration (1 and 5%) is not effective. At high concentration of 10%, anti-proliferative activity is effective. Cytotoxic effect of water extract of the rhizome of Curcuma zedoaria at the concentration of 10% changes the Hela cell morphology, but not cell wall rupture. High concentration of ethanol extract causes Hela cells to change its shape, rupture the cell walls, and fragment the cells.